Jaminan Fidusia Secara Online Dengan Objek Hak Cipta Dalam Perjanjian Kredit - Bella Anggraini; Bambang Eko Turisno (Magister Kenotariatan Universitas Diponegoro, 2023)
AbstractCopyright has an economic value that can be assessed and provides material benefits for the creator so that it can be used as an object of guarantee. Copyright holders must register their creations with the Directorate General of Intellectual Property Rights (Directorate General of Intellectual Property Rights under the auspices of the Minister of Law and Human Rights) to be recorded in the General Register of Copyrights. Fiduciary agreements must be based on good faith and must be in accordance with what has been agreed. Copyright is still difficult to be used as an object of fiduciary guarantee in a credit agreement, because there is no institution or regulation that regulates the assessment of copyright itself. The complexity of determining the assessment of the economic value of copyright as intellectual property.Keyword: fiduciary guarantee; credit agreement; copyrightAbstrakHak cipta memiliki nilai ekonomi yang dapat dinilai serta memberikan keuntungan materi bagi penciptanya sehingga dapat dijadikan objek jaminan. Pemegang hak cipta harus mendaftarkan ciptaannya tersebut ke Direktorat Jenderal Hak kekayaan Intelektual (Ditjen Hak Kekayaan Intelektual yang berada di bawah naungan Menteri Hukum dan Hak Asasi Manusia) untuk dicatat dalam Daftar Umum Hak Cipta. Perjanjian fidusia harus dilandasi dengan itikad baik dan harus sesuai dengan apa yang telah disepakati. Hak cipta masih sulit untuk dijadikan objek jaminan fidusia dalam perjanjian kredit, oleh karena belum adanya sutatu lembaga atau peraturan yang mengatur tentang penilaian dalam hak cipta itu sendiri. Rumitnya menentukan penilaian mengenai nilai ekonomis hak cipta sebagai kekayaan intelektual.Kata kunci: jaminan fidusia; perjanjian kredit; hak cipta